Integrating Religious Moderation Into English Learning Materials: A Narration of Two Teachers - Puspitasari, Dewi; Khasanah, Nur; Nofianto, Norma; Rosyid, Ocid Abdul; Maulida, Chusna (Linguists : Journal of Linguistics and Language Teaching, 2024)
This study narrates the journey of integrating religious moderation into English learning materials through the lens of narrative inquiry. By focusing on the experiences of two English teachers, the research explores the challenges and successes encountered during the incorporation of religiously moderate perspectives into their curriculum. Through detailed interviews, the teachers' narratives reveal their motivations, strategies, and the pedagogical implications of blending religious moderation with language instruction. The findings underscore the importance of cultural sensitivity and the potential for such integration to enhance students' holistic understanding of language and intercultural competence. This narrative inquiry not only contributes to the field of English for Specific Purposes learning material but also offers valuable insights for educators seeking to harmonize religious values with academic objectives.